2018
DOI: 10.37603/2250.7728.v21.n1.19388
|View full text |Cite
|
Sign up to set email alerts
|

Estudio comparativo de dos sitios aldeanos del primer milenio d.C. en Tucumán, Argentina

Abstract: En este trabajo realizamos una comparación de los entornos materiales construidos en dos asentamientos del primer milenio d.C. ubicados en el piedemonte meridional y oriental de las Cumbres Calchaquíes. Estos casos son el de La Bolsa 1, en el sector norte del valle de Tafí, y Mortero Quebrado, en la cuenca alta del río Anfama. Nos interesa particularmente caracterizar las similitudes y diferencias en diversos aspectos y escalas de las estructuras objetivas y prácticas de agentes que se materializan a través de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
14

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 3 publications
0
3
0
14
Order By: Relevance
“…On the other hand, there are no signs of public spaces or hierarchical places such as plazas or mounds that have been observed in Yocavil (Tarragó, 1987(Tarragó, , 2011. This configuration maintains a clear continuity with those of the first Millennium of the Era in the area (Salazar & Molar, 2017).…”
Section: An Approach To Landscape Construction During Rdpmentioning
confidence: 56%
See 2 more Smart Citations
“…On the other hand, there are no signs of public spaces or hierarchical places such as plazas or mounds that have been observed in Yocavil (Tarragó, 1987(Tarragó, , 2011. This configuration maintains a clear continuity with those of the first Millennium of the Era in the area (Salazar & Molar, 2017).…”
Section: An Approach To Landscape Construction During Rdpmentioning
confidence: 56%
“…We propose that in Anfama during the RDP, the groups settled in the region maintained some local principles of use of space and ways of doing that characterized the first Millennium occupations, although they appropriate new regional parameters in the production and consume of ceramics. In fact, we observed that the RDP archaeological sites reproduce the dispersed and symmetrical settlement pattern of previous moments (see López Lillo & Salazar, 2015;Salazar & Molar, 2017) and that they also appear to maintain somelocal pottery techniques (see Franco, 2019). Those elements allowed us to think in the importance of domestic spaces for the construction of social relations and exchange networks in a regional scale.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…Si bien, como se desarrolló brevemente en este acápite, no se puede dejar de considerar a Anfama dentro de un contexto más general de ocupaciones humanas del primer milenio en la región (Salazar y Molar, 2017;Oliszewski, 2017;Scattolin, 2010;Berberián y Nielsen, 1988); corresponde también marcar las características particulares que presenta el valle, que lo diferencian de sectores vecinos en lo que respecta a condiciones climáticas y ambientales, y cómo estas pudieron influir en la dinámica particular de la práctica alfarera.…”
Section: Figura 2i Ubicación De Anfamaunclassified
“…Las distintas ocupaciones del primer milenio de la Era identificadas por el EASCC permiten insertar a El Sunchal dentro de un paisaje aldeano más amplio, que implicó la coexistencia de múltiples ocupaciones sincrónicas, las cuales comparten un sustrato material y cultural común (para mayores precisiones de los sitios ver también Salazar et al, 2016;Salazar y Molar, 2017;Salazar, 2017;Montegú, 2016Montegú, y 2018.…”
Section: Ii) Ocupaciones Del Primer Milenio De La Era En Anfamaunclassified